La integración escolar de alumnos con necesidades educativas especiales : Entre la realidad y el deseo - Gerardo Echeita (Universidad de La Rioja, 2013)
In this paper the lntegration Programme for Pupils wtih Special Educational Needs developped by the Ministry of Education and Culture is valued. Some factors involved in the perceived negative scope are analized, particulary regarding with social attitudes of satisfaction about present results, design conditions and lack of curriculum development policy